2010
DOI: 10.1016/j.jcrs.2010.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in anterior chamber depth and intraocular pressure after phacoemulsification in eyes with occludable angles

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 21 publications
(23 reference statements)
3
60
1
Order By: Relevance
“…Shin et al [24] found a significant increase in ACD and a significant reduction in IOP (p<0.01) after cataract surgery when they compared non-glaucomatous eyes with open angles or with occludable angles. This deepening in the AC was inversely related to preoperative ACD in the occludable-angle group (P<0.01).…”
Section: Discussionmentioning
confidence: 98%
“…Shin et al [24] found a significant increase in ACD and a significant reduction in IOP (p<0.01) after cataract surgery when they compared non-glaucomatous eyes with open angles or with occludable angles. This deepening in the AC was inversely related to preoperative ACD in the occludable-angle group (P<0.01).…”
Section: Discussionmentioning
confidence: 98%
“…4,5,11,12 Recently, anterior chamber anatomic parameters measured by different anterior segment imaging modalities such as AS-OCT have become the center of focus to predict the amount of IOP reduction after cataract surgery. Most of these studies evaluated the anterior chamber angle and ACD as determinants of IOP drop.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] This effect seems to be more pronounced in narrow angles (NAs) compared with open angles (OAs). 2,[4][5][6]10 Several studies have been performed to predict the amount of IOP change after cataract surgery on the basis of preoperative factors. These studies have shown that the higher the preoperative IOP and the shallower the anterior chamber depth (ACD), the more pronounced is the change in IOP after cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Proposed mechanisms include relief of subclinical or intermittent angle narrowing, 7,8 widening of the trabecular meshwork spaces and Schlemm canal, 3,4 and the effects of ultrasound on trabecular meshwork cytokine release. 9 Accurate prediction of the IOP change after cataract surgery is of great interest because it would help in the proper selection of cataract surgery, incisional glaucoma surgery, or a combined procedure.…”
mentioning
confidence: 99%